1, 2-Dihalodigermenes bearing bulky Eind groups: synthesis, characterization, and conversion to halogermylenoids. Issue 3 (18th December 2017) - Hayakawa, Naoki; Sugahara, Tomohiro; Numata, Yasuyuki; Kawaai, Hotaka; Yamatani, Kenta; Nishimura, Shogo; Goda, Shun; Suzuki, Yuko; Tanikawa, Tomoharu; Nakai, Hidetaka; Hashizume, Daisuke; Sasamori, Takahiro; et al.
Abstract : We present the transformation of low-coordinate germanium(ii ) compounds. Abstract : 1, 2-Dihalodigermenes, ( E )-(Eind)XGeGeX(Eind) (X = Br and Cl), bearing the fused-ring bulky Eind group (Eind = 1, 1, 3, 3, 5, 5, 7, 7-octaethyl- s -hydrindacen-4-yl) have been isolated as orange-yellow crystals by the ligand redistribution reaction between the diarylgermylene, (Eind)2 Ge:, and GeX2 ·dioxane in toluene via the cleavage and recombination of the Ge–C and Ge–X bonds. The dihalodigermenes have a GeGe double bond character in the crystalline state, but dissociate into halogermylenes, (Eind)XGe:, in solution. The addition of excess LiBr to the THF solution of the bromogermylene, (Eind)BrGe:, led to the formation of an equilibrium mixture containing the lithium bromogermylenoid, [Li + ][(Eind)GeBr2 ] − . The bromogermylenoid can be isolated as a cryptand-separated potassium ion pair, [K + (crypt-222)][(Eind)GeBr2 ] −, which has been structurally characterized.